Are residents receiving the training needed within their residency programs to optimally manage patients with diabetes?. Issue 4 (19th May 2021) - Morales, Javier; Kuritzky, Louis; Lavernia, Frank; Santiago, Michael
ABSTRACT: Objective : Diabetes is a prevalent and growing problem in the United States (U.S.); primary care physicians need to be prepared to initiate and progressively advance treatment. The objective of this study was to understand how diabetes management is taught in U.S. Family Medicine (FM) and Internal Medicine (IM) residency programs. Methods : Invitations to complete an online survey were sent via postal mail to U.S. FM and IM residency programs in 2019. Results : Directors/associate directors from 68 FM residencies and 66 IM residencies completed the online survey out of 645 (10.5%) and 505 (13.1%) programs, respectively. Most respondents rated cardiovascular disease and risk management in diabetes as 'very important' (90%), but only about half (47%) did so for newer generation insulin analogs and 27% for digital health technologies. About two-thirds of programs cover non-insulin options for type 2 diabetes (66%) and types of insulin (63%) to a great extent, but only about one-third of programs cover social determinants of health (36%) and pre-diabetes (35%) to this degree. Many programs report plans to expand training on cardiovascular disease and diabetes (59%), but only 32% plan to expand training on digital technology for diabetes care. Lack of faculty time and competing priorities are cited as being the biggest barriers to expanding diabetes training. Conclusions : Our study found that the current U.S. FM and IM residency program diabetes curricula are dominantly oriented toward cardiovascular disease and 'traditional' insulins. A variety of training materials and resources could help overcome some of the current barriers to curriculum expansion of other important components of diabetes care that may help future physicians successfully manage diabetes with newer generation insulin and glucose monitoring technologies. Abbreviations : U.S: United States; PCP: Primary Care Physician; FM: Family Medicine; IM: Internal Medicine; CGM: Continuous Glucose Monitor; AAFP: American Academy of Family Physicians; ACGME: Accreditation Council for Graduate Medical Education; U/mL: units per milliliter; CME: Continuing Medical Education.